Proof: Get Iterate Parent 48

Let's prove the following theorem:

if the following are true:
  • expression state at time 48 = "iterate_args"
  • arguments stack at time 48 = [ [ self, [ ] ], [ [ 5, [ ] ], [ [ ], [ ] ] ] ]
  • parent stack at time 48 = [ self.x, [ __add__(self.x, 5), [ self."x" = __add__(self.x, 5), [ ] ] ] ]

then parent stack at time 49 = [ self.x, [ __add__(self.x, 5), [ self."x" = __add__(self.x, 5), [ ] ] ] ]

Proof:

View as a tree | View dependent proofs | Try proving it

Given
1 expression state at time 48 = "iterate_args"
2 arguments stack at time 48 = [ [ self, [ ] ], [ [ 5, [ ] ], [ [ ], [ ] ] ] ]
3 parent stack at time 48 = [ self.x, [ __add__(self.x, 5), [ self."x" = __add__(self.x, 5), [ ] ] ] ]
Proof Table
# Claim Reason
1 parent stack at time (48 + 1) = parent stack at time 48 if expression state at time 48 = "iterate_args" and arguments stack at time 48 = [ [ self, [ ] ], [ [ 5, [ ] ], [ [ ], [ ] ] ] ], then parent stack at time (48 + 1) = parent stack at time 48
2 parent stack at time (48 + 1) = [ self.x, [ __add__(self.x, 5), [ self."x" = __add__(self.x, 5), [ ] ] ] ] if parent stack at time (48 + 1) = parent stack at time 48 and parent stack at time 48 = [ self.x, [ __add__(self.x, 5), [ self."x" = __add__(self.x, 5), [ ] ] ] ], then parent stack at time (48 + 1) = [ self.x, [ __add__(self.x, 5), [ self."x" = __add__(self.x, 5), [ ] ] ] ]
3 48 + 1 = 49 48 + 1 = 49
4 parent stack at time (48 + 1) = parent stack at time 49 if 48 + 1 = 49, then parent stack at time (48 + 1) = parent stack at time 49
5 parent stack at time 49 = [ self.x, [ __add__(self.x, 5), [ self."x" = __add__(self.x, 5), [ ] ] ] ] if parent stack at time (48 + 1) = parent stack at time 49 and parent stack at time (48 + 1) = [ self.x, [ __add__(self.x, 5), [ self."x" = __add__(self.x, 5), [ ] ] ] ], then parent stack at time 49 = [ self.x, [ __add__(self.x, 5), [ self."x" = __add__(self.x, 5), [ ] ] ] ]

Comments

Please log in to add comments